Insights into the potential release of dissolved organic matter from different agro-forest waste-derived hydrochars: A pilot study. (15th October 2021) - Ji, Rongting; Su, Lianghu; Cheng, Hu; Wang, Yuan; Min, Ju; Chen, Mei; Li, Haidong; Chen, Sujuan; Wang, Saier; Yu, Guo; Zhang, Longjiang; Han, Jiangang
Abstract: Hydrochar derived from biowaste has recently attracted widespread interest for high-performance environmental applications. However, the potential release behaviors of dissolved organic matter from hydrochar (HDOM) in various environments are still unknown. In this study, three agro-forest waste-derived hydrochars were prepared, and the element composition, pore structure, thermal recalcitrance, functional groups and surface properties were characterized. Four extractants and two extraction temperatures were applied to simulate the possible environments. UV–visible spectroscopy and excitation-emission matrix spectra with parallel factor analysis were applied to evaluate the chemical properties of HDOM. The results showed that large quantities of HDOM could be leached, and the concentration of dissolved organic carbon ranged from 32.62 to 404.81 g kg −1 . Fulvic acid-like substances (34.01–60.38%), humic acid-like substances (12.53–37.31%) and protein-like substances (13.46–45.68%) were identified in HDOM. Alkaline and high-temperature conditions enhanced the release of HDOM with high aromaticity and hydrophobicity as well as a high molecular weight. Combined with principal component analysis, the order of the main influencing factors on the specific chemical properties of HDOM was extractant > feedstock > temperature. These findings confirmed that released HDOM would result in significant influences on soil remediation, carbon sequestration, wastewater treatment, and soil fertility improvement during the application of hydrochar. The environmental behavior of HDOM needs to be further investigated in the future. Graphical abstract: Image 1 Highlights: Large amounts of DOM could be released from agro-forest waste-derived hydrochars. HDOM was mainly composed of humic acid-like, fulvic acid-like and protein-like substances. High temperature and alkaline conditions could promote the release of HDOM and change the proportion of components. Order of the main influencing factors on HDOM release was extractant > feedstock > temperature.